The best mystery stories of the year 2021 - Child, Lee; Penzler, Otto; Allyn, Douglas; Allyn, Jim, 1944-; Bracken, Michael; Burke, James Lee, 1936-; Edwards, Martin, 1955-; Floyd, John M.; Freimor, Jacqueline; Gaylin, Alison; Grafton, Sue; Kemprecos, Paul; et al. (Mysterious Press, an imprint of Penzler Publishers, 2021)
"Under the auspices of New York City's legendary mystery fiction specialty bookstore, The Mysterious Bookshop, and aided by Edgar Award-winning anthologist Otto Penzler, international bestseller Lee Child has selected the twenty most suspenseful, most confounding, and most mysterious short stories from the past year, collected now in one entertaining volume."--Amazon.